Propriedades de transporte de spins polarizados em heteroestruturas semicondutoras - Pacobahyba, Luiz Henrique (Universidade Federal de São Carlos, 2009)
In this work we used the technique of scattering matrix to calculate the transmissivity of polarized spins in a semiconductor symmetrical double-barrier heterostruture. The dynamics of carriers is described by effective mass approximation applied to models of Dresselhaus and Bychkov-Rashba. In the former case, the hamiltonian was studied in its full form, free of approximations. Both models describe interactions of type Spin-orbit, which is basically a coupling between the orbital angular moment of the electron with its magnetic moment of spin. This type of coupling as a consequence creates a splitting of some levels of energy, initially degenerate, resulting in a spectrum of energy more complex than that obtained without taking it into account such interactions. The transmissivity is calculated as a function of some parameters, for the type InAs=GaSb=InAs=GaSb=InAs. All results are compared with literature, and provide new information about the systems. The effects of spin-orbit interactions of Rashba and Dresselhaus show is very favorable to engineering in the manufacture of .lter spin and spintronic devices, as well as the injection of spin in quantum wells and semiconductor detectors based on non-magnetic asymmetric double barrier.
Keywords: Física da matéria condensada; Transporte de spins polarizados; Spintrônica; Tunelamento ressonante; CIENCIAS EXATAS E DA TERRA::FISICA